Determination of oral and dental health knowledge and behaviors of primary school students - Turan, Mehmet; Bozkurt, Eyup; Erdogan, Ramazan (Revista Ecorfan, 2022)
This research was carried out to determine primary school students' knowledge, attitudes, and behaviors about oral and dental health. The research group consisted of students studying in the 3rd and 4th grades in the primary schools in the central district of Elazig', and the sample group consisted of 420 (218 Female, 202 Male) volunteer students studying in the 3rd and 4th grades in the primary schools in the central district. As a data collection tool, a questionnaire form was applied in which the demographic information of the students and their oral and dental health knowledge and behaviors were questioned. The data were analyzed by using the SPSS package program and the significance was accepted as p < 0.05. When the research group's oral health knowledge and behaviors were examined, it was found that the majority of the students (69.6%) brushed their teeth twice or three times a day, and the majority had good oral and dental health. It was determined that 84.5% of the students brushed their teeth after meals and before going to bed to prevent their teeth from decaying. It was determined that most parents of the participants in the research group (289 people) had the habit of brushing their teeth, and the participants learned the first information about brushing from their families. It was seen that there was a significant difference between the frequency of tooth brushing of the participants and the gender variable, and in the frequency of brushing teeth twice or more times a day, women brushed their teeth more than men. It was determined that there was a significant difference between the frequency of students' brushing their teeth and the age variable, and the rate of tooth brushing increased as the age value increased. Consequently, to create a healthy society, informing and taking precautions about preventive oral and dental health from an early age will contribute to reducing oral and dental diseases that may occur in the future.
Keywords: Knowledge; Primary school students; Dental health; Oral health; Healthy society